Applyng Technology-Based Learning Through Online Media Blog To Teach Writing - Dian Nashrul Munif (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2017)
At this time, the development of Information and Communication Technology (ICT) in various fields is very rapid and is viewed as both a necessity and an opportunity. In the field of English language teaching, for example, the development of ICT can provide a new dimension for developing literacy media for learners. ICT is able to provide creative opportunities for young writers. Good writing skills are important for learners' future. However, writing instruction is still commonly conducted in a conventional manner, where teachers often ask learners to write directly without guiding them through the writing process. In many cases, the topics provided are limited, making them less interesting and less challenging, thereby reducing opportunities for exploration, innovation, and creativity. Furthermore, teachers often serve as the only evaluators of students' writing, resulting in limited feedback and interaction throughout the writing process. One way to improve the quality of writing instruction and learners' writing skills through the use of ICT is by utilizing blogs (online journals). Blogs provide an online platform where learners can write about topics they find interesting, edit their work, publish it, and even use it as a medium for sharing ideas with others. It is believed that writing through blogging can provide access to a real audience, encourage better editing, promote innovation, exploration, and creativity, foster more dynamic interaction, enhance literacy skills, and support collaborative learning through teamwork.